Two mutations in the HMG-box with very different structural consequences provide insights into the nature of binding to four-way junction DNA. - Teo, S H (1995)
Mutation of the highly conserved tryptophan residue in the A-domain HMG-box of HMG1 largely, but not completely, destroys the protein tertiary structure and abolishes its supercoiling ability, but does not abolish structure-specific DNA binding to four-way junctions. Circular dichroism shows that the protein has some residual alpha-helix (< 10%) and does not re-fold in the presence of DNA. Structure-specific DNA binding might therefore be a property of some primary structure element, for example the N-terminal extended strand, which even in the unfolded protein would be held in a restricted conformation by two, largely trans, X-Pro peptide bonds. However, mutation of P5 or P8 of the A-domain to alanine does not abolish the formation of the (first) complex in a gel retardation assay, which probably arises from binding to the junction cross-over, although the P8 mutation does affect the formation of higher complexes which may arise from binding to the junction arms. Since mutation of P8 in the W49R mutant has no effect on structure-specific junction binding, we propose that some residual alpha-helix in the protein might be involved, implicating this element in the interactions of HMG-boxes generally with DNA.